Accidental Instrument Aspiration in Geriatric Patient: A Case Report - Garima Arora; Satish Sane; Shabnam Negi; Anil Richhawal; Harshraj Gawande; Sreeja Nair (Medicine and Medical Research: New Perspectives Vol. 6, 2024)
Background: This case report presents a detailed account of an incident involving the aspiration of an endodontic file during a routine dental procedure, highlighting the critical importance of preventive strategies, early diagnosis, and prompt intervention to manage such emergencies effectively. Case Overview: The patient, a 68-year-old female with a known hyperactive gag reflex, underwent a routine endodontic procedure. During the procedure, a sudden brisk movement led to the unexpected aspiration of an endodontic file. Due to the patient’s pronounced gag reflex, traditional preventive measures such as the use of a rubber dam and gauze pack were not feasible. Immediately following the aspiration, the dental team attempted to induce coughing by positioning the patient to expel the foreign object naturally; however, these efforts were unsuccessful. Diagnostic and Therapeutic Intervention: Prompt radiographic imaging, including chest radiography, was conducted to locate the aspirated file, which was found lodged in the larynx. The patient was immediately referred for a laryngoscopic examination, during which the file was successfully retrieved using Magill’s forceps. The timely intervention prevented potentially serious complications, such as respiratory distress, airway obstruction, or secondary infections, which could have arisen from the retained foreign body. Conclusion and Implications: This case underscores the critical importance of vigilance and adherence to protective protocols during dental procedures, particularly in patients with known risk factors, such as a hyperactive gag reflex. The report emphasizes the necessity of implementing preventive strategies, including the use of physical barriers when feasible and ensuring proper patient positioning, to reduce the risk of foreign body aspiration. Furthermore, it highlights the need for dental practitioners to be prepared for immediate action in the event of such emergencies, including having a clear protocol for emergency management and rapid access to diagnostic tools and referral services. This case serves as a valuable reminder of the potential risks associated with dental procedures and the importance of proactive measures to ensure patient safety.